Annealing device - WANG PENG; LI LEI (2017)
The utility model relates to an annealing device. This annealing device includes: box, sliding component, supporting part and heater. The sliding component sets up in the box, the supporting part with the sliding component is connected, the supporting part is followed the sliding component cunning advance to in the box or the roll -off arrive outside the box, the heater sets up on the supporting part. Above -mentioned annealing device when the heater need be safeguarded, can make heater and supporting part together outside the roll -off box to pull down the heater from the supporting part. Can avoid heater and box other inside parts to collide each other like this to guarantee the safety of heater. 本实用新型涉及种退火装置。该退火装置包括：箱体、滑移件、支撑部及加热器。所述滑移件设置在所述箱体内；所述支撑部与所述滑移件连接，所述支撑部随所述滑移件滑进到所述箱体内或滑出到所述箱体外；所述加热器设置在所述支撑部上。上述退火装置，当加热器需要维护时，可以使加热器和支撑部起滑出箱体外，并且将加热器从支撑部上拆下。这样可以避免加热器与箱体内部的其它部件相互碰撞，从而保证加热器的安全。